NASIONALISME DALAM PENDIDIKAN ISLAM - Lukman Hakim (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2012)
The distinction between santri (Islam) and nationalist became the burning issue again. This is triggered by the acts of violence and terrorism done by a group/some Indonesian Muslims who have backgrounds as santri in pesantren. As a result, people tend to consider that santri (Muslims) no longer has a love for his homeland (nationalism). This paper intends to provide an overview that historically, Islam was actually very nationalistic, particularly in the Dutch colonial times. Many rebellions came previously from Santri before the nationalists do, such as Diponegoro war and Banten war. The studies of nationalist attitude of the santri was approached with character studies. In addition, figures of the study were Abdul Hasbullah and Ahmad Dahlan. By studying both national modern and Islamic education figures, it is expected that Muslims realize the spirit of loving their motherland as well as the nationalism as the part of religious doctrine of Muslims.